An investigation of how grade 10 learners make sense of concepts on refraction of light through exploring their cultural beliefs/everyday experiences about the rainbow : a case study - Homateni, Rauha Kau Ndahalomwenyo (Rhodes University, Faculty of Education, Department of Education, 2013)
This study took place at a private high school in the Kavango region with my 32 grade 10B learners as the research participants. Its objective was to investigate how the grade 10 learners make sense of concepts on refraction of light through exploring their cultural beliefs/everyday experiences about the rainbow. This research study was essentially triggered by my own classroom experience of teaching the topic on refraction of light. In order to achieve the goal of this research, a qualitative case study located within an interpretive paradigm was adopted. To gather data I used multiple data gathering techniques such as brainstorming session, learners conducting interviews in the community, practical activities and focus group interviews. This resulted in descriptive data that qualified to be analyzed in a qualitative way. The themes that emerged from the generated data were coded using upper letter cases and various colours. A methodological triangulation was employed by using multiple data generation techniques. Member checking during focus group interviews also ensured validity in this case study. The findings of this study revealed that the use of learners' cultural beliefs/everyday experiences can be used to enhance learner engagement, meaning making and conceptual development during the science lessons. In addition, the ways in which practical activities are designed and presented to learners in the science classroom determine learners' participation and conceptual attainment. Therefore, based on my research findings, I recommend that teachers need to be trained to be able to elicit and integrate learners' cultural beliefs/everyday experiences in conjunction with hands-on practical activities which focus on conceptual development during their science lessons. However, although this study had many benefits, it also showed that it is not easy to close the gap between learners' prior everyday knowledge and school science. This warrants further research.
Keywords: Science -- Study and teaching (Secondary) -- Namibia; Light -- Study and teaching; Light -- Study and teaching